2014
DOI: 10.1021/om500001h
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Studies of Cyclometallated Ruthenium(II) Compounds: New Applications for Ruthenium Dyes

Abstract: The antiproliferative activity of four Ru(II) dyes incorporating the cyclometallated ligand phpy − (deprotonated 2-phenylpyridine) have been tested against HeLa cells. All of the compounds exhibit cytotoxic activity similar to that of cisplatin. The most active compound, [Ru(phpy)(bpy)-(dppn)] + (4; bpy = 2,2′-bipyridine, dppn = benzo[i]dipyrido-[3,2-a:2′,3′-c]phenazine), is 6 times more active than the platinum drug, and it is able to disrupt the mitochondria membrane potential. In addition, [Ru(phpy)(biq) 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 55 publications
1
60
0
Order By: Relevance
“…[23][24][25][26] Turro's group showed that coordinatively saturated Ru II dyes displayed high cytotoxicity towards cancer cells. [27] While most of the above drug screenings were performed against 2D cell monolayers, to the best of our knowledge only one application of MCTSs in ruthenium-based anticancer drug development has been reported. [28] Our group has focused on the use of transition metal complexes as anticancer drugs or luminescent biological probes.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Turro's group showed that coordinatively saturated Ru II dyes displayed high cytotoxicity towards cancer cells. [27] While most of the above drug screenings were performed against 2D cell monolayers, to the best of our knowledge only one application of MCTSs in ruthenium-based anticancer drug development has been reported. [28] Our group has focused on the use of transition metal complexes as anticancer drugs or luminescent biological probes.…”
Section: Introductionmentioning
confidence: 99%
“…22 On the other hand, Ru(II)-polypyridyl complexes are known to generate reactive oxygen species (ROS) up on irradiation into their MLCT band in the visible region of the spectrum. [23][24][25][26] As outlined above, such ROS species damage biomolecules and are therefore cytotoxic to living cells. [27][28][29] Since these two complexes are functionalized with amino acid moieties to enhance cellular internalization and possess well-defined photophysical/physicochemical properties, their capability to photo-induced damage to the DNA and function as cytotoxic agents was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…6> In the similar 2-phenylpyridine bipyridine cycloruthenium five-membered ring compounds 2.43a -2.43d (Fig. 7) [27], the cytotoxicity of these compounds toward HeLa cells is given as 2.43a: 34 ± 3 μM, 2.43b: 57 ± 7 μM, 2.43c: 51 ± 8 μM and 2.43d: 7 ± 1 μM, respectively. Most of the compounds exhibit cytotoxic activity similar to that of cisplatin (40 ± 9 μM).…”
Section: Applications Of Five-membered Ring Products Of Cyclometalatimentioning
confidence: 94%
“…7> agents [27]. The cyclometalated five-membered osmium derivatives of 2-Phenylpyridine, 2-phenylpyrazoline, 2-phenyloxazine and 2,6-bis(2-pyridyl)benzene, 2.44a -2.57b (Fig.…”
Section: Applications Of Five-membered Ring Products Of Cyclometalatimentioning
confidence: 99%